Antarctic Toothfish Dissostichus mawsoni in the South Orkney Islands: Using Otolith Chemistry to Test Current Hypotheses About Nursery Areas and Demographic Units - Paulina Carimán; Edwin J. Niklitschek; Cristóbal Garcés; Mathieu Leisen; Fernando Barra; Rurik Romero (Biology)
We used otolith chemistry to test and complement current hypotheses regarding habitat use and connectivity between Dissostichus mawsoni sub-populations in Area 48 of the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR). Sagittal otoliths from 45 fish sampled near the South Orkney Islands were analysed. Their elemental (Li, Na, Mg, Cr, Mn, Sr, Sn, and Ba relative to Ca) and isotopic (δ18O and δ13C) signatures were examined in both the nuclear and marginal regions, representing juvenile and adult stages. Potential nursery habitats were geo-located by comparing observed and expected δ18O values. Chemical differences between the nuclear and marginal regions indicated ontogenetic migrations to deeper offshore habitats, suggesting a distinct habitat shift between 11 and 13 years of life. The data supported the existence of two nursery origins contributing to the study area’s population. However, the exact locations of these origins remain unclear and did not provide direct support for the hypotheses currently under consideration by the CCAMLR. Therefore, further assessment of the connectivity between nursery and adult habitats, as well as spawning site fidelity, is necessary before ruling out alternative hypotheses.